2021
DOI: 10.1272/jnms.jnms.2021_88-415
|View full text |Cite
|
Sign up to set email alerts
|

Capecitabine Plus Bevacizumab as First-Line Therapy for Patients with Metastatic Colorectal Cancer and Poor Performance Status

Abstract: Background: Benefit of chemotherapy for patients with metastatic colorectal cancer is well known, however, that for those patients with poor performance status is little known. Patients and methods: We retrospectively evaluated efficacy of chemotherapy with capecitabine and bevacizumab for patients with poor PS (PS 3). Results: Seven patients were included and the median age of the patients was 82 years (range, 65-91 years). The response was not ascertained; nonetheless, the disease control rate was 83.3%. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The optimal strategy for maintenance therapy in patients with mCRC remains controversial. In previous retrospective studies, capecitabine combined with bevacizumab as a first‐line therapy for the mCRC patients with poor performance status (PS: 3) had a disease control rate of 83.3% and could provide favourable PFS and OSrates 6 . For elderly mCRC patients (PS: 2) who were not suitable for irinotecan and oxaliplatin‐containing chemotherapy regimens with an average age of over 75.5 years old, the combination of bevacizumab and capecitabine couldsignificantly improve OS and PFS rates, without excessively serious toxic effects 7 …”
Section: What Is Known and Objectivementioning
confidence: 99%
See 1 more Smart Citation
“…The optimal strategy for maintenance therapy in patients with mCRC remains controversial. In previous retrospective studies, capecitabine combined with bevacizumab as a first‐line therapy for the mCRC patients with poor performance status (PS: 3) had a disease control rate of 83.3% and could provide favourable PFS and OSrates 6 . For elderly mCRC patients (PS: 2) who were not suitable for irinotecan and oxaliplatin‐containing chemotherapy regimens with an average age of over 75.5 years old, the combination of bevacizumab and capecitabine couldsignificantly improve OS and PFS rates, without excessively serious toxic effects 7 …”
Section: What Is Known and Objectivementioning
confidence: 99%
“…In previous retrospective studies, capecitabine combined with bevacizumab as a first‐line therapy for the mCRC patients with poor performance status (PS: 3) had a disease control rate of 83.3% and could provide favourable PFS and OSrates. 6 For elderly mCRC patients (PS: 2) who were not suitable for irinotecan and oxaliplatin‐containing chemotherapy regimens with an average age of over 75.5 years old, the combination of bevacizumab and capecitabine couldsignificantly improve OS and PFS rates, without excessively serious toxic effects. 7 A recent study also demonstrated that the co‐therapy of bevacizumab and capecitabine showed curative effects on mCRC patients who had failed at least two chemotherapy regimens, with a disease control rate of 65% and an effective prolonged survival rate.…”
Section: What Is Known and Objectivementioning
confidence: 99%